Withaferin A alleviates ethanol-induced liver injury by inhibiting hepatic lipogenesis. (February 2022) - Hamada, Keisuke; Wang, Ping; Xia, Yangliu; Yan, Nana; Takahashi, Shogo; Krausz, Kristopher W.; Hao, Haiping; Yan, Tingting; Gonzalez, Frank J.
Abstract: Withaferin A (WA) is a natural steroidal compound with reported hepatoprotective activities against various liver diseases. Whether WA has therapeutic effects on alcoholic liver disease has not been explored. A binge alcoholic liver injury model was employed by feeding C57BL/6J mice an ethanol (EtOH) diet for 10 days followed by an acute dose of EtOH to mimic clinical acute-upon-chronic liver injury. In this binge model, WA significantly reduced the binge EtOH-induced increase of serum aminotransaminase levels and decreased hepatic lipid accumulation. Mechanistically, WA decreased levels of hepatic lipogenesis gene mRNAs in vivo, including Srebp1c, Fasn, Acc1 and Fabp1 . In EtOH-treated primary hepatocytes in vitro, WA decreased lipid accumulation by lowering the expression of the lipogenesis gene mRNAs Fasn and Acc1 as well as decreasing hepatocyte death. In the established binge alcoholic liver injury model, WA therapeutically reduced the EtOH-induced increase of serum aminotransaminase levels as well as hepatic lipid accumulation. These results demonstrate that WA reduces EtOH-induced liver injury by inhibiting hepatic lipogenesis, suggesting a potential therapeutic option for treating alcoholic liver injury. Graphical abstract: Withaferin A improves binge alcoholic liver injury by decreasing hepatic lipogenesis and reducing lipid accumulation in ethanol-treated mice and primary hepatocytes. Image 1 Highlights: WA prevented binge alcoholic-induced liver injury by decreasing hepatic lipogenesis. WA reduced the lipogenesis in ethanol-treated primary hepatocytes. WA therapeutically improved liver injury induced by binge ethanol.